Ecosystem-Based Adaptation Through the Lens of Community Preferences - Duguma, L.; Duba, D.; Muthee, K.; Minang, Peter A.; Bah, A.; Nzyoka, J.; Malanding, J. (2020)
Ecosystem-based Adaptation (EbA) practices are people-centered, nature-based solutions which aim to ensure that communities can cope with the adverse effects of climate change. These practices utilize biodiversity and ecosystem services as part of the wider adaptation strategies. In recent years, communities across the globe have embraced different EbA pathways as part of their adaptation option. This necessitated a comprehensive feasibility assessment to establish the most practical options in different context in The Gambia. This technical brief looks at EbA practices based on community preferences, gender choices, values and incentives, potential enablers and barriers, as well as policy and institutional frameworks based on findings from the EbA project in The Gambia